Emergency Procurement in Nigeria : Mitigating the Corruption Risks (Strathmore Law Journal, 2025)
This article unpacks the concept of emergency procurement and why it is highly susceptible to corruption. It examines the grounds upon which procuring entities may carry out emergency procurement as stipulated in the Public Procurement Act of 2007 (the PPA), which is the primary legal framework governing public procurement at the federal level of government in Nigeria. The author suggests that the provisions of the PPA should be amended to allow procuring entities to apply competitive negotiation and framework agreements in the award of emergency procurement where appropriate, in addition to the direct procurement method. Furthermore, the author recommends that in line with the provisions of the PPA, all procuring entities that carry out emergency procurement should be mandated to submit comprehensive reports of their procurements to the Bureau of Public Procurement (the Bureau). Similarly, the Bureau should carry out post-emergency audits on such procurement to ascertain the justification for emergency procurement, and whether due process was followed. The Bureau should also take appropriate punitive action against those culpable, where it finds any evidence of corruption.